REINTERPRETASI KETIDAKSANTUNAN PRAGMATIK - Rahardi, R. Kunjana (Universitas Muhammadiyah Surakarta, 2013)
Enormous imbalance of study between language impoliteness and language politeness has become serious concern among those who regard pragmatics important field in language learning. Impoliteness constitutes existing phenomena in most societies and cultures but it has so far been regarded as outside the study of pragmatics itself. This paper is meant to trigger the study of this seemingly-new phenomenon that the study of pragmatics becomes more and more extensive in Indonesia. The restriction of the available theories of this pragmatic phenomenon should not hinder the study of pragmatics.